PRIMARY SCHOOL STUDENTS CIRCUMCISION COMPETIONS DEVELOPMENT (Multidisciplinary Journal of Science and Technology, 2025)
The formation of speartical competes of students in the process of modern education has given information about the development of their communication skills, forming critical and creative thinking and effective communication in society. One of the urgent tasks facing the education system is also mentioned that a sporatic Competence is connected with modern approaches and technologies